PREVALENCE OF MALOCCLUSION IN STUDENTS OF KALINYAMAT KULON 3 PRIMARY SCHOOL, MARGADANA DISTRICT, TEGAL CITY - Wardana, Puspitarini Nindya; Utari, Tita Ratya; Ardiansyah, M.Shulchan; Paryontri, Bayu Ananda; Haqita, Adellaurin Nisa (Indonesian Journal of Dentistry, 2025)
Background: Malocclusion is a deviation in the alignment of teeth on the dental arch, leading to dental and oral health problems. Malocclusion can occur in both mixed and permanent dentitions. The causes of malocclusion vary, including genetic factors and environmental factors such as bad habits. Public awareness regarding bad habits and general oral health care is inadequate in coastal areas. This study aims to determine the prevalence of malocclusion among students at SD Kalinyamat Kulon 3, located in the Margadana District, Tegal City.Method: The research is an observational descriptive study using total sampling. The sample size in this study is 71 respondents. Angle’s Classification of Malocclusion was used to assess each sample.Outcome: The results show a prevalence of 58% for Angle Class I Malocclusion, 38% for Angle Class II Malocclusion, and 4% for Angle Class III Malocclusion. The data distribution by gender shows that 42.25% of females and 57.75% of males exhibit malocclusion.Conclusion: This study concludes that Angle Class I Malocclusion has the highest prevalence among students.